Red blood cell distribution width is associated with poor clinical outcome in acute cerebral infarction - Kim, Jinkwon; Kim, Young Dae; Song, Tae-Jin; Park, Ji Hye; Lee, Hye Sun; Nam, Chung Mo; Nam, Hyo Suk; Heo, Ji Hoe (Thrombosis and Haemostasis, 2012)
Increased red blood cell distribution width (RDW), which is a marker of anisocytosis, is associated with mortality and cardiovascular events in the general population and in patients with heart failure or coronary heart disease. We investigated whether RDW in acute cerebral infarction is predictive of functional outcome and mortality. A total of 847 consecutive patients with first-ever acute cerebral infarction who presented to the emergency department within seven days of symptom onset were enrolled in this study. We investigated the association of RDW with poor functional outcome (modified Rankin Scale >2) and all-cause mortality at three months, as well as survival time for one year after stroke onset. Multivariate logistic regression revealed that higher RDW was independently associated with poor functional outcome (adjusted odds ratio [OR], 1.222 per 1% increment in RDW, 95% confidence interval [CI] 1.059–1.409, p=0.006) and all-cause death (adjusted OR, 1.395 per 1% increment in RDW, 95% CI 1.168–1.665, p<0.001) at three months after stroke onset. RDW was an independent predictor of survival in multivariate Cox-proportional regression model (adjusted hazard ratio, 1.328 per 1% increment in RDW, 95%CI 1.178–1.498, p<0.001). The addition of RDW to a survival model significantly increased predictability for survival across the entire follow-up period (weighted average of the area-under the curves, 0.858 vs. 0.841, p<0.05). In conclusion, higher RDW measured in cases of acute stage cerebral infarction was associated with poor functional outcome and mortality. RDW may be used as a biomarker for the prediction of long-term outcomes in patients with acute cerebral infarction.
Keywords: Cerebrovascular disease; stroke; mortality; red blood cell distribution width (RDW)